Summary of the research The effect of a sports diet program according to a training curriculum on some functional and biochemical indicators for young Romanian wrestlers - Shuaib, Jamal Mohammad; Judi, Suzan Khalifa (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to prepare a sports diet program according to a training curriculum in some functional and biochemical indicators for the individuals in the research sample, as well as to identify the effect of the sports diet program according to a training curriculum in some functional and biochemical indicators for the individuals in the research sample, as well as to identify the effect of the training curriculum without using the sports diet program in Some functional and biochemical indicators for the individuals in the research sample, as the two researchers used the experimental approach with three groups to suit the nature of the research problem, as the research sample was chosen intentionally from the young wrestling players in the Diyala word for the weight category ( 54, 58, 63) kg, whose number is (18) wrestlers out of (22) wrestlers, they were randomly divided into three groups, two experimental groups and the other control group, and for each group (6) wrestlers, (2) wrestlers per weight, as the first group carried out The sports nutritional program with the training curriculum, while the second group implemented the training curriculum only, and the control group implemented the trainer curriculum, and thus the percentage of the sample (81.818%) of the original community was formed, in addition to using the appropriate means, tools and devices, and the exploratory experiment was conducted, after which a Tribal tests for the three groups, then apply the diet Athlete and the training curriculum, and then conduct a meta-tests of the three groups, and then dump the data were processed and statistically, and then presented and analyzed and discussed, and the researchers reached several conclusions, namely :• The sports diet program with the training curriculum has given a clear effect on some functional and biochemical indicators for the first group members . The training curriculum without using the sports diet program also gave a clear effect on some functional and biochemical indicators for the second group .• All functional and biochemical indicators achieved a clear effect of the three groups. The first experimental group achieved the preference, then the second experimental group followed, then the control group .The researchers reached several recommendations : • Take advantage of the sports diet program prepared by the researchers by wrestlingteams . • Benefiting from the training curriculum prepared by the researchers in the training of wrestling teams, especially the emerging wrestlers .• Carrying out similar research on different samples and other functional variables .